2003
DOI: 10.1021/ma0302098
|View full text |Cite
|
Sign up to set email alerts
|

Phase Behavior of PS−PVME Nanocomposites

Abstract: The influence of nanometer thick, highly anisotropic organically modified layered silicate (montmorillonite) on the phase behavior of deuterated polystyrene (dPS) and poly(vinyl methyl ether) (PVME) is investigated by a combination of small-angle neutron scattering (SANS) and a two-dimensional combinatorial method based on light scattering and corroborated by single-point static cloud-point light scattering. The presence of layered silicates up to a volume fraction of 0.04 is found to leave the phase diagram e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(54 citation statements)
references
References 30 publications
(52 reference statements)
3
51
0
Order By: Relevance
“…It is conceivable that besides a positive impact of the particles on the viscosity development of the continuous polymer phase (as observed in the rheological behavior of a reference system, see below), the LDH particles might simply form physical obstacles for the moving interface between the demixing polymer phases. This latter effect was simulated for binary polymer systems comprising spherical hard particles and corroborating morphologies were observed with several silica beads filled (Karim et al, 1999) and smectite filled non crystalline polymer blends (Yurekli et al, 2003(Yurekli et al, , 2004. Indeed CLSM and XRD studies revealed that the PES (and possibly both the polar components PURx and MF resin) readily intercalates the LDH galleries in the initial waterborne coating material while the particular shape of the micron sized aggregates of polymer intercalated LDH particles slowly disappears during the air drying process.…”
Section: Intrinsically Incompatible Matrixsupporting
confidence: 66%
“…It is conceivable that besides a positive impact of the particles on the viscosity development of the continuous polymer phase (as observed in the rheological behavior of a reference system, see below), the LDH particles might simply form physical obstacles for the moving interface between the demixing polymer phases. This latter effect was simulated for binary polymer systems comprising spherical hard particles and corroborating morphologies were observed with several silica beads filled (Karim et al, 1999) and smectite filled non crystalline polymer blends (Yurekli et al, 2003(Yurekli et al, , 2004. Indeed CLSM and XRD studies revealed that the PES (and possibly both the polar components PURx and MF resin) readily intercalates the LDH galleries in the initial waterborne coating material while the particular shape of the micron sized aggregates of polymer intercalated LDH particles slowly disappears during the air drying process.…”
Section: Intrinsically Incompatible Matrixsupporting
confidence: 66%
“…This phenomenon should be attributed to the change of network structure in the blend caused by interfacial adhesion. Note that PVME molecules (dispersive solubility parameter, " d = 15.5 MPa 1/2 , and polar solubility parameter, " p = 7.1 MPa 1/2 ) are much more polar than PS molecules (" d = 18.1 MPa 1/2 and " p = 1.1 MPa 1/2 ) [45] so that PVME chains tended to be preferentially absorbed on the nanoparticles surface. On the other hand, due to great thermodynamic work of adhesion between PS and PVME [46], the PS/PVME interface is still relatively stable under the shear forces during mixing so that nanoparticles more likely exist in PVME but not at the interphase between PS and PVME, forming the final core-shell structure which has been confirmed in scanning electron microscopy results obtained by Gharachorlou and Goharpey [46].…”
Section: -Express Polymer Letters Vol5 No9 (2011) 799-808mentioning
confidence: 99%
“…The thermodynamic implications were proposed to govern by simultaneous action of two mechanisms: selective absorption of one of polymers on the solid surface and redistribution of macromolecules with respect to their molecular weights between the bulk and the boundary layer (in the vicinity of filler surface) and the alteration of the interaction parameter between polymer constituents. Likewise, Yurekli et al [18] studied the effects of layered silicate on the phase behavior of polystyrene (PS)/poly(vinyl methyl ether) (PVME) blends. They observed that the phase transition boundary was not considerably changed by adding 0.04 volume fraction of nanoclay.…”
Section: Introductionmentioning
confidence: 99%